Berberine attenuates sunitinib-induced cardiac dysfunction by normalizing calcium regulation disorder via SGK1 activation. (May 2023) - Li, Congxin; Wu, Wenting; Xing, Jiahui; Yan, Wei; Zhang, Jiali; Sun, Jinglei; Zhang, Zhihan; Qiu, Suhua; Xu, Yanfang; Wang, Xianying
Abstract: Sunitinib (SNT)-induced cardiotoxicity is associated with abnormal calcium regulation caused by phosphoinositide 3 kinase inhibition in the heart. Berberine (BBR) is a natural compound that exhibits cardioprotective effects and regulates calcium homeostasis. We hypothesized that BBR ameliorates SNT-induced cardiotoxicity by normalizing the calcium regulation disorder via serum and glucocorticoid-regulated kinase 1 (SGK1) activation. Mice, neonatal rat cardiomyocytes (NRVMs), and human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) were used to study the effects of BBR-mediated SGK1 activity on the calcium regulation disorder caused by SNT as well as the underlying mechanism. BBR offered prevention against SNT-induced cardiac systolic dysfunction, QT interval prolongation, and histopathological changes in mice. After the oral administration of SNT, the Ca 2+ transient and contraction of cardiomyocytes was significantly inhibited, whereas BBR exhibited an antagonistic effect. In NRVMs, BBR was significantly preventive against the SNT-induced reduction of calcium transient amplitude, prolongation of calcium transient recovery, and decrease in SERCA2a protein expression; however, SGK1 inhibitors resisted the preventive effects of BBR. In hiPSC-CMs, BBR pretreatment significantly prevented SNT from inhibiting the contraction, whereas coincubation with SGK1 inhibitors antagonized the effects of BBR. These findings indicate that BBR attenuates SNT-induced cardiac dysfunction by normalizing the calcium regulation disorder via SGK1 activation. Graphical abstract: Image 1 Highlights: Sunitinib (SNT) causes left ventricular systolic dysfunction. SNT inhibition of SGK1 activity is an important cause of cardiotoxicity. Berberine activates PI3K-SGK1 activity to inhibit cardiotoxicity. Berberine normalizes calcium regulation disorder via SGK1 activation.